Pengembangan Perangkat Pembelajaran Matematika Problem Posing Tipe Post Solution Posing Pada Materi Statistika - Vanny Algafari; Nyoman Sridana; Muhammad Turmuzi; Sripatmi Sripatmi (Pendidikan Matematika FKIP Universitas Mataram, 2021)
The purpose of this research was to obtain a practical Problem Posing type of Post Solution Posing learning tool according to the Mathematics teacher at SMPN 1 Batulayar. This type of research is qualitative research by giving questionnaires and interviews. The subjects in this study were the Mathematics Teachers at SMPN 1 Batulayar. The object of this research is the practicality of the learning tools, namely the Learning Implementation Plan and Student Worksheets with the post solution posing problem posing type model. The instruments used in this study were questionnaires and interviews. The questionnaire made is a structured questionnaire with answers that are not free and has been validated. Interviews were conducted in a structured manner according to understanding. Based on the results of the analysis in this study, it shows that the learning tools for the post solution posing model are very practical and easy to apply.